1920
DOI: 10.1093/qjmed/os-14.53.1
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Steatorrhoea

Abstract: IN this paper we present a clinical and analytical study of a case of eongenital steatorrhoea and compare it with the only previous example of the condition as yet reported. The term steatorrhoea, which has sometimes been used to cover all cases passing an obvious excess of fat in the stools (fatty diarrhoea, diarrhoea alba), is here used in its more correct and restricted sense, namely, as indicating a passage from the bowel of separated liquid fat which congeals on cooling (Butterstiihle). This phenomenon, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1924
1924
1958
1958

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The clinical picture is highly characteristic, but it must be emphasized that an accurate history is essential, and close questioning may be required to obtain this, as noted by Miller and Perkins (1920). The disease should be suspected in all cases of chronic nutritional difficulty and chronic respiratory infection in children, and specific questions asked about appetite, weight-gain, the character of the stools in regard to number, size, and smell, the exact date of onset of any abnormality noted, and the family history, especially of infantile deaths, In a number of cases the abnormality of the stools, while present from early infancy, becomes more obvious when solids are added to the diet or even later, and this overshadows the history.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical picture is highly characteristic, but it must be emphasized that an accurate history is essential, and close questioning may be required to obtain this, as noted by Miller and Perkins (1920). The disease should be suspected in all cases of chronic nutritional difficulty and chronic respiratory infection in children, and specific questions asked about appetite, weight-gain, the character of the stools in regard to number, size, and smell, the exact date of onset of any abnormality noted, and the family history, especially of infantile deaths, In a number of cases the abnormality of the stools, while present from early infancy, becomes more obvious when solids are added to the diet or even later, and this overshadows the history.…”
Section: Discussionmentioning
confidence: 99%
“…Henderson (1945) recorded one case and MacGregor and Rhaney (1948) two cases in siblings. Previously, under the title of congenital steatorrhoea, Miller and Perkins (1920) and Cockayne (1933) each described one probable case of fibrocystic disease, and Clarke and Hadfield (1924) a proved case, for necropsy showed the pancreatic lesions which are now associated with this disease. It is unlikely that the case described by Garrod and Hurtley (1913) under the same title was one of fibrocystic disease, since Garrod (1920) subsequently reported that this patient was of normal development and activity at the age of 14 years.…”
mentioning
confidence: 99%
“…In all the present cases the diagnosis was made clinically and was never disproved by subsequent examination of the duodenal juice or by necropsy. The clinical picture is highly characteristic, but it must be emphasized that an accurate history is essential, and close questioning may be required to obtain this, as noted by Miller and Perkins (1920). The disease should be suspected in all cases of chronic nutritional difficulty and chronic respiratory infection in children, and specific questions asked about appetite, weight-gain, the character of the stools in regard to number, size, and smell, the exact date of onset of any abnormality noted, and the family history, especially of infantile deaths, In a number of cases the abnormality of the stools, while present from early infancy, becomes more obvious when solids are added to the diet or even later, and this overshadows the history.…”
Section: Discussionmentioning
confidence: 99%